Successful Human Spermatogonial Stem Cells Homing In Recipient Mouse Testis After In Vitro Transplantation And Organ Culture - Mahdi Mohaqiq; Mansoureh Movahedin; Zohreh Mazaheri; Naser Amirjanati (Cell Journal, 2018)
Objective In vitro transplantation (IVT) of spermatogonial stem cells (SSCs) is one of the most recent methods in transplantation in recent decades. In this study, IVT and SSCs homing on seminiferous tubules of host testis in organ culture have been studied.